The Formation of Agro-Food Clusters as a Competitiveness Growth Factor - Dorzhieva, Elena V.; Dugina, Evdokia L. (International Journal of Economics and Financial Issues, 2015)
The article deals with the formation of agro-food clusters enhancing the competitiveness and sustainability of the regional economy. The author studies the development features of agroindustrial complex of the region, its nature, and clarifies the economic content of the agro-food cluster concept, as well as defines the prerequisites and principles of clusters formation in the Russian agroindustrial complex and identifies features of their functioning. It is proved that the development of agro-food clusters entails both socio-economic and environmental benefits due to the composite nature of the agroindustrial complex and regional specificity. It is revealed that cooperation and integration, as well as the interaction of small, medium and large businesses are quite effective in the agricultural sector, because the different forms of management have their own unique niches, targeted at consumers with different income levels and quality requirements of food products. The composite nature of the agroindustrial complex and the implementation of cluster policy should lead to the blurring of sectorial corporate and technological boundaries in a number of production sectors, as well as to reduction of price disparities, raising the prestige and productivity of agricultural jobs, development of social sphere of the village, the transition from technological structure to innovation aiming at the protection of the environment. The author proposes to merge large economic entities into agri-industrial cluster, while small and medium size companies – into agri-ecological cluster, based on the principles of organic agriculture production. This will contribute to both the sustainable development of rural areas and increasing the competitiveness of the region. Keywords: cluster, competitiveness, agroindustrial complex, region, sustainable development. JEL Classifications: R11; Q13; Q18